(untitled) (Indian Journal of Psychology & Education, 2021)
How to make safety a way of life, whether this objective is a myth or reality? This paper is an exploration in this direction involving 540 HSE professionals using focused group discussions/interviews and webinars. Implications are drawn toward this objective as well as reflections on the existing safety culture and its challenges and solutions thereof. Hopefully, this exploratory effort would help nearing the objective.